Narečne tvorjenke s priponskim obrazilom -ica iz pomenskega polja 'človek' (po gradivu za SLA 1) - Horvat, Mojca (Jezikoslovni zapiski, 2013)
This article shows a possible secondary interpretation of the dialect material in volume 1 of Slovenski lingvistični atlas (Slovenian Linguistic Atlas, SLA 1), published in 2011. It focuses on derivatives with the suffix -ica thatwere classified according to the morpheme structure of the suffix and the part-of-speech category of the motivated word. The frequency and geographical distribution of the expressions analyzed are determined using a word-formation map
Keywords: besedotvorje; meaning formation; pomenotvorje; priponsko obrazilo -ica; Slovene; Slovene dialects; Slovene langauge; Slovenian Linguistic Atlas; slovenska narečja; Slovenski lingvistični atlas; slovenščina; suffix -ica; word formation